THE FORMATION OF FIQH PANDEMIC IN MALAYSIA: STUDY ON THE RELATIONSHIP BETWEEN MA?LA?A? AND MAFSADAH - Lukman Abd Mutalib, Wan Abdul Fattah Wan Ismail, Ahmad Syukran Baharuddin, Abdul Manan Ismail, Mohd Soberi Awang, Setiyawan Gunardi, Siti Fatimah Salleh, Muhammad Hazim Ahmad (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The desired goal behind the obligation of a law is referring to the maqasid syariah. It is very important to master this knowledge especially to understand and interprete the Islamic texts. The cardinal principle is generally aims to preserve the five basic necessities of human life, namely preserving the religion, life, intellect, lineage, and property. Any effort that supports these necessities is known to be maslahah, and anything that negates them is known to be mafsadah. The concept of maslahah and mafsadah has always been the main backbone for the scholars in determining the law. During the pandemic COVID-19 hit in Malaysia, various Syariah rulings (fatwas) have been issued by the authorities at the state and federal levels to protect the Muslims affairs. The rulings are issued after considering the maslahah and mafsadah to be faced by Muslims in Malaysia. This study was conducted to identify the role of maslahah and mafsadah in influencing the Syariah rulings related to COVID-19 pandemic in Malaysia as well as showing how the process takes place (taky?ful fiqh?). This study is qualitative in nature, using a library approach to collect primary and secondary data and then analyse it by content analysis. The results show that the principles of maslahah and mafsadah play a big role in determining the Syariah rulings in the COVID-19 pandemic situation as well as the need to set a clear standard of maslahah and mafsadah so that the rulings produced are accurate, precise and not made it on whim.